Evaluating the impact of trust and security on e-wallet adoption: insights from the UTAUT2 model in Indonesia - Riza, Aulia Alka; Aditya, Addin (Jurnal Simantec, 2025)
The rapid expansion of financial technology (Fintech) in Indonesia has led to a significant rise in e-wallet usage. Despite this growth, the key factors influencing user acceptance remain insufficiently explored, particularly regarding the integration of trust and security within the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) framework. This research seeks to analyze the behavioral intentions of e-wallet users by incorporating perceived trust and perceived security into the UTAUT2 model. A quantitative approach is employed, gathering primary data from Indonesian e-wallet users through a structured online survey. The study applies a purposive sampling method, ensuring that all participants have prior experience with e-wallet usage. To examine the relationships among performance expectancy, social influence, facilitating conditions, hedonic motivation, perceived trust, perceived security, and behavioral intention, Multiple Regression Analysis is utilized. The findings indicate that perceived trust and perceived security play a crucial role in shaping users' behavioral intentions regarding e-wallet adoption. However, factors such as performance expectancy, social influence, facilitating conditions, and hedonic motivation do not significantly influence behavioral intention. This suggests that users prioritize security and reliability over external social influences or entertainment value when deciding to adopt e-wallets. Despite its contributions, this study has limitations, particularly its focus on a single e-wallet platform and sample size constraints, which may affect the broader applicability of the findings. Future research should expand its scope by examining multiple e-wallet platforms, incorporating qualitative insights, and analyzing the impact of regulatory policies on trust and security to enhance the understanding of e-wallet adoption dynamics.Keywords: Behavioral Intention, E-Wallet Adoption, Fintech, Perceived Trust, Perceived Security, UTAUT2